FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN OBESITAS PADA KARYAWATI PERUSAHAAN DI BIDANG TELEKOMUNIKASI JAKARTA TAHUN 2017 - Wegarti Sikalak; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Obesity arises as a result of energy input that exceeds energy expenditure until most of the excess energy will be stored as fat and the body weight increases. When viewed from the gender, women are more likely to be obese due to lower female metabolism. The purpose of this study was to determine the factors related with the obesity in female employees. The type of this research was analytical descriptive with cross sectional design. The population of the research was female employees in PT Telecommunication Jakarta in 2017 as 66 people. Sampling technique was purposive sampling so get it a sample of 42 people. Anthropometric measurements were conducted in body weight and height, characteristic questionnaire filling, physical activity questionnaire using Global Physically Activity Questionnaire (GPAQ), filling stress questionnaire using Depression Anxiety and Stress Scale (DASS), filling the recall form for 2 days for nutritional adequacy. The data analysis used chi square test. After doing the research, it was found 42 respondents out of total 66 respondents. The result showed, there were 28 (66,7%) of obese female employees (IMT≥27 kg/m2). The result showed that there was a relation between marital status (p= 0.011), offspring (p = 0.01) with obesity of female employees in PT Telecommunication Jakarta in 2017. There was no relation of age, income, nutritional status, physical activity and stress with obesity of female employees in PT Telecommunication Jakarta in 2017. It was suggested for female employees do routine physical activity.